The taxonomic status and sister group relationship of the cardinalfish species Jaydia striatodes (Percomorphaceae: Apogonidae) - Yu, Zhengsen; Song, Na; Han, Zhiqiang; Gao, Tianxiang; Shui, Bonian; Gon, Ofer (Zootaxa, 2016)
Two similar cardinalfish species, Jaydia striatodes and J. striata, were compared morphologically and genetically, using the fragment of cytochrome oxidase subunit I (COI) gene of the mitochondrial DNA. The results confirmed the validity of both species and their sister group relationship. The species formed well-supported monophyletic clades that were distinctly separate with mean sequence divergence of 12.2%. Jaydia striatodes is distinct in having 4–5 + 12–13 gill rakers; 3 + 11–12 developed gill rakers; 9 gill rakers on the first ceratobranchial; 3–9 weak serration at the angle of preopercular edge; and a usually blackish distal half of anal fin. Jaydia striatodes was recorded for the first time from Beibu Gulf, China, and from Vietnam.